Perdamaian Negatif dalam Kegagalan Resolusi Dewan Keamanan PBB dalam Konflik Suriah 2011-2019 - Pattipeilhy, Shary Charlotte Henriette (Jurnal Hubungan Internasional, 2021)
Since the first shot fired over a decade ago, there has been no comprehensive solution to the Syrian Conflict. Despite countless efforts and interventions carried out by the international community, perpetual peace still seems to be a distant dream. This includes resolutions and initiatives passed by the United Nations Security Council (UNSC). This article would explain further on why these actions has minimum impact, therefore failed to attain stability in Syria. Utilizing the principle of Peace By Peaceful Means by Johan Galtung, along with concepts related to International Conflict Resolutions, the results find that the UNSC has given the wrong diagnosis, prognosis, and treatment to the Syrian Conflict. This is reflected within narratives found in resolutions passed by the UNSC that are laden with nuance of negative peace. A lot of stress has been put upon ‘resolving’ the Syrian Conflict to bring peace. Meanwhile, conflict is not a negation of peace. The author thus suggest that stability in Syria is more likely to be attainable if resolutions reflect more upon the positive peace paradigm; by means of ‘managing’ and ‘transforming’ the Syrian conflict to restore the peace.